2015
DOI: 10.1097/qai.0000000000000543
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Coital Dilution in Accra, Ghana

Abstract: Background Coital dilution, the reduction in the coital frequency per partner when an additional ongoing partner is added, may reduce the transmission potential of partnership concurrency for HIV and other sexually transmitted infections. Empirical estimates of dilution, especially dilution of sexual acts unprotected by condoms, are needed to inform prevention research. Methods Sexually active adults in Accra, Ghana were recruited in a multi-stage household probability sample. Degree (number of ongoing partn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Other studies have shown similar rates of CD4 + cell counts persisting below 200 cells/μl, 350 and 500 cells/μl, and a continued high rate of clinical events during ART [3234,37,38]. Even in settings where there is routine monitoring of viral load, data show that although the majority of those who are virologically suppressed achieve good immune recovery, up to 40% still exhibit SO-IR [39,40].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Other studies have shown similar rates of CD4 + cell counts persisting below 200 cells/μl, 350 and 500 cells/μl, and a continued high rate of clinical events during ART [3234,37,38]. Even in settings where there is routine monitoring of viral load, data show that although the majority of those who are virologically suppressed achieve good immune recovery, up to 40% still exhibit SO-IR [39,40].…”
Section: Discussionmentioning
confidence: 92%
“…A variety of different definitions have been used in clinical trials [33,34], observational cohorts [31,32], pathogenesis studies [19,35] to define suboptimal recovery. In this analysis, we defined SO-IR as failure to attain three different CD4 + cell count thresholds during the first 5 years of first-line antiretroviral therapy: 200 cells/μl (SO-IR200), below which individuals remain at particular risk of life-threatening opportunistic infections [22,23]; 350 cells/μl (SO-IR350) – the recommended threshold for ART initiation in the WHO 2010 guidelines [7] and 500 cells/μl (SO-IR500) – the recommended threshold for ART initiation in WHO 2013 guidelines [9].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Degree terms were stratified by sex, as men exhibited both higher mean degree and prevalence of concurrency. 12 A parametrical term was used to model sex-asymmetry in age homophily typical of heterosexual partners in SSA: persons tended to select partners similar in age, but asymmetrically, as men were older than their female partners (an average 5.4 years in MHG).…”
Section: Dynamic Sexual Networkmentioning
confidence: 99%
“…This translated to a reduction in the mean duration by 0.9 years; the expected number of lifetime partners between the MHG estimates (9.6) and simulations after this adjustment (10.1) were similar. 12 …”
Section: Dynamic Sexual Networkmentioning
confidence: 99%